Gender Differences in Current Received during Transcranial Electrical Stimulation - Russell, Michael; Goodman, Theodore; Wang, Qiang; Groshong, Bennett; Lyeth, Bruce G. (Frontiers in Psychiatry, 2014)
Low current transcranial electrical stimulation is an effective but somewhat inconsistent tool for augmenting neuromodulation. In this study, we used 3D MRI guided electrical transcranial stimulation (GETS) modeling to estimate the range of current intensities received at cortical brain tissues. Combined T1, T2, Proton Density MRIs from 24 adult subjects (12 male and 12 female) were modeled with virtual electrodes placed at F3, F4, C3 and C4. Two sizes of electrodes 20 mm round and 50 x 45 mm square were examined at 0.5, 1 and 2 mA input currents. The intensity of current received was sampled in a one centimeter sphere placed at the cortex directly under each scalp electrode. There was a tenfold range in the current received by individuals. A large gender difference was observed with female subjects receiving significantly less current at targeted parietal cortex than male subjects when stimulated at identical current levels (P <0.05). Larger electrodes delivered somewhat larger amounts of current then the smaller ones (P <0.01). Electrodes in the frontal regions delivered less current than those in the parietal region (P<0.05). There were large individual differences in current levels the subjects received. Analysis of the cranial bone showed that the gender difference and the frontal parietal differences are due to differences in cranial bone. Males have more cancellous parietal bone and females more dense parietal bone (p<0.01). These differences should be considered when planning transcranial electrical stimulation studies and call into question earlier reports of gender differences due to hormonal influences.